(untitled) (Altre Modernità, 2016)
The present article exposes the results of the Chilean student movement, which through 2011 was protagonist of a prolonged mobilization about the vindication of a public, free and education of a good quality on all the educational system levels. The study of the speech here developed sets out to understand the construction of the meaning that the dominant newspaper El Mercurio de Valpara’so made about the mentioned movement, from the thematic diversity perspective, discourse complexity and performative which represented in its informative discourse the news students activities. After the application of a critic analysis of the discourse matrix to a sample of 263 informative texts, published between May and December of 2011, and analyze the local and global meanings, explicit and implicit of the text, it goes deep here the analysis of the subtle formal structures which emerge of the text-context relation, showing as result the significant matrixes implied on the articulation of four kind of discourse: the ahistoric, the one of authority, the one of criminalization, and the one of the show business.